Why marry early? Parental influence, agency and gendered conflict in Tanzanian marriages. (21st October 2022) - Baraka, Jitihada; Lawson, David W; Schaffnit, Susan B; Wamoyi, Joyce; Urassa, Mark
Abstract: Abstract: Global health interventions increasingly target the abolishment of 'child marriage' (marriage under 18 years, hereafter referred to as 'early marriage'). Guided by human behavioural ecology theory, and drawing on focus groups and in-depth interviews in an urbanising Tanzanian community where female early marriage is normative, we examine the common assumption that it is driven by the interests and coercive actions of parents and/or men. We find limited support for parent–offspring conflict. Parents often encouraged early marriages, but were motivated by the promise of social and economic security for daughters, rather than bridewealth transfers alone. Moreover, forced marriage appears rare, and adolescent girls and young women (AGYW) were active agents in the transition to marriage, sometimes marrying against parental wishes. Support for gendered conflict was stronger. AGYW were described as being lured into unstable relationships by men misrepresenting their long-term intentions. Community members voiced concerns over these marriages. Overall, early marriage appears rooted in limited options, encouraging strategic, but risky choices on the marriage market. Our results highlight plurality and context dependency in drivers of early marriage, even within a single community. We conclude that engaging with the importance of context is fundamental in forging culturally sensitive policies and programs on early marriage.